Effect of Canal Bank Filtration on Quality of Water Long Hyderabad City - Kandhar, Imdad Ali; Khaskheli, Ghous Bux; Sahito, Abdul Razaque; Mahar, Rasool Bux (Mehran University Research Journal of Engineering and Technology, 2016)
The focus of the present study was to examine the effect of canal bank filtration on the quality of water and the geological settings along the banks of canals at the shallow depth aquifers. The four Model wells were drilled at different locations of the Line channel, Pinyari and phulali canals in the study area. The samples of soil were collected throughout drilling of the model wells for the analysis of grain size distribution .In addition to this, canal water and model well water samples were collected and analyzed for the water quality characteristics during winter and summer seasons. The analysis of soil and water samples reveals that the ground water is influenced by the grain size distribution, hydraulic conductivity and the location of the model Wells. The model well that has higher percentage of 0.075 mm of grain size distribution(hydraulic conductivity between 10-25 ft/day) was more suitable for the filtration of the canal water through its banks, followed by 0.15 mm of grain size distribution (hydraulic conductivity > 25ft/ day). Moreover, the present study also shows that the canal water filtration is suitable in terms of total alkalinity, nitrate-nitrogen, total iron and pH to get the potable water at the location near upstream of the canal, especially in the summer season.